Peran Departemen Corporate Communication dalam Melakukan Sosialisasi Nilai Perusahaan melalui Media Internal - Cendera Rizky Bangun (Ultimacomm: Jurnal Ilmu Komunikasi, 2016)
A strong internal communication system can encourage loyalty and increase labor productivity. The system plays important role in retaining employees in a company and makes them feel connected with the company's vision. This study explores the role of PT Darya Varia Laboratoria Tbk's Corporate Communication division in communicating the corporate culture to employees through its internal communication program. The method used in this study is qualitative method with a post-positivist paradigm. The result reveals the company’s value of BERSATU, or literally translated as UNITED. The value try to be instilled in every activity of its employees that involves the company, both directly and indirectly. This research concludes that the Corporate Communication Department of PT Darya-Varia is the door that manage information flow. This department must be able to filter information and determine which should be distributed, and how a message can be well received. Keywords: Corporate communication, internal communication, corporate values, socialization